Major pathologic response to alectinib in ALK-rearranged adenocarcinoma of the lung - Naoko Imanishi; Kazue Yoneda; Akihiro Taira; Yoshinobu Ichiki; Naoko Sato; Masanori Hisaoka; Fumihiro Tanaka (Surgical Case Reports)
Abstract Background Alectinib is a highly selective tyrosine kinase inhibitor of anaplastic lymphoma kinase (ALK) and provided a significantly prolonged progression-free survival compared with chemotherapy in patients with advanced non-small cell lung cancer (NSCLC) harboring rearrangements of the ALK gene. Here, we present the first surgical case of ALK-rearranged lung adenocarcinoma with major pathological response in resected specimens after treatment with alectinib. Case presentation A 65-year-old female with clinical stage IIIA-N2 ALK-rearranged adenocarcinoma originating from the left lower lobe presented. Involvement of lower para-tracheal node was pathologically confirmed by endobronchial ultrasound-guided biopsy. Alectinib was prescribed, as the patient may not tolerate radiotherapy due to a mental illness. After 3 months’ treatment with alectinib, a remarkable radiological and metabolic response was achieved. The patient did not tolerate further continuation of alectinib treatment, and surgery was performed without any morbidity. Only < 10% tumor cells were viable in all resected specimens, indicating major pathological response to alectinib. Conclusions Salvage surgery after alectinib treatment may be safe and effective for initially unresectable NSCLC harboring ALK-rearrangements.